Investigation into Shock Control and Drag Reduction Characteristics of Opposing Plasma Synthetic Jet in Mach 8 Flow - Xudong Zhang; Hao Dong; Xingyu Cao; Yan Zhou; Wei Xie; Wei Song; Yan Wang (Aerospace)
Plasma synthetic jet (PSJ) is widely employed in flow control due to its advantages of zero-mass and fast-response. A novel measurement method for high-frequency dynamic drag variation was adopted in a Mach 8 wind tunnel experiment, demonstrating that the opposing PSJ can achieve a maximum drag reduction of 40.27% and an average drag reduction of 13.25% within one discharge cycle. Subsequently, the numerical method was verified in detail and the effects of different discharge energies and nozzle diameters on the drag reduction characteristics of the opposing PSJ were studied. The results show that an increase in discharge energy is beneficial for the drag reduction characteristics of the opposing PSJ, although the efficiency remains relatively low. In contrast, increasing the nozzle diameter enhances the average drag reduction but significantly reduces the duration of effective control. The drag reduction mechanism of the opposing PSJ can be attributed to the combined effects of pushing the strong bow shock away to form a weaker oblique shock, followed by the reattachment of the shock downstream.